Exports of non‐stun meat: clarity and continued campaigning. (1st September 2018) - Fishwick, John
Abstract : BVA has been calling for a ban on non‐stun slaughter in the UK for some time and the millions of animals whose welfare is still compromised by this practice each year remains a major concern.